RUAF Cities Farming for the Future Programme Anglophone West Africa Region project report 2005-2008 - Cofie, Olufunke O.; Otchere-Labri, Theophilus; Schuetz, Tonya; Abraham, Ernest M.; Kumassah, R. (International Water Management Institute, 2008)
This is a report on the fourth and final year of the RUAF-CFF programme activities in West Africa Anglophone region, coordinated by the International Water Management Institute (IWMI), Ghana. This report documents the activities implemented as well as the results, outcomes and impacts in all focus cities within the region from January 2005 to December 2008. The cities are: a. Pilot cities: Accra, Ghana, Freetown, Sierra Leone, and Ibadan, Nigeria in sequential order of entry and intervention; b. Partner (or dissemination) cities: Tamale, Tema and Cape Coast in Ghana; and Akure in Nigeria, all at completion stages of pilot project implementation in their respective cities.